MEASURING AND ANALYZING FINANCIAL HEALTH INDICATORS TO REDUCE FINANCIAL FRAGILITY -AN ANALYTICAL STUDY OF A NUMBER OF PRIVATE COMMERCIAL BANKS LISTED ON THE IRAQ STOCK EXCHANGE (American Journal of Business Management, Economics and Banking, 2023)
The research focused on measuring and analyzing indicators of financial health in reducing financial vulnerability An analytical study of a number of private commercial banks listed on the Iraq Stock Exchange The research problem focused on the main question "Can the financial health of Iraqi banks be measured and analyzed?" The research aimed to measure and analyze the financial health of a number of private commercial banks to identify banks that enjoy better financial health to reduce financial fragility. The research used the descriptive analytical method using programs EXCELL and Evewis, and the research concluded, the results showed a long-term relationship and the sign is negative, which means that the relationship is inverse between (the rate of return on assets X1, the rate of return on deposits X2) and the financial fragility index (Y) and at a probability level of less than 5%, and the research recommended By investing more at the rate of return on deposits and return on assets.